MINERVA: A CubeSat for demonstrating DNA damage mitigation against space radiation in C. elegans by using genetic modification - Sumeth Klomchitcharoen; Tanchanok Tangwattanasirikun; Sean Gallup; Noparin Smerwong; Peetimon Arunwiriyakit; Pisitchai Tachavises; Jin Tangkijngamwong; Pichamon Phatthanaanukun; Benjamard Jirapanyalerd; Siripak Chattanupakorn; Visarut Rungpongvanich; Norawit Nangsue; et al. (Heliyon, 2022)
The ideas of deep-space human exploration, interplanetary travel, and space civilizations are becoming a reality. However, numerous hindrances remain standing in the way of accomplishing these feats, one of which is space ionizing radiation. Space ionizing radiation has become the most hazardous health risk for long-term human space exploration, as it can induce chromosomal damage and epigenetic changes. The Minerva mission aims to demonstrate cutting-edge technology to inhibit DNA damage against deep-space radiation exposure by using genetic modification. The concept of the experiment is to transform a creature with radiation intolerance into a transgenic organism that is radiation-tolerant. In this mission, Caenorhabditis elegans (C. elegans) will be genetically engineered with a protein-coding gene associated with DNA damage protection called damage suppressor (Dsup). Dsup is a nucleosome-binding protein from the tardigrade Ramazzottius varieornatus that has a unique ability to prevent DNA damage. This paper describes the feasibility of Minerva CubeSat, which will venture out to cis-lunar orbit with a biosensor payload capable of sustaining and culturing C. elegans under space environment conditions for 4 months. The mission will set in motion a paradigm shift corresponding to future space medicines and how they will be developed in the future, introducing a platform suitable for future experiments in the fields of space biology. Ultimately, the paramount objective of Minerva will be to test the limits of genetic engineering and incorporate it into the arduous journey of human perseverance to overcome the boundaries of space exploration—a vital step in making Mars colonization safe.